PECULIARITIES OF INTERNATIONAL SOURCES OF ENVIRONMENTAL LAW OF THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2020)
This article discusses the theoretical and practical aspects of the international sources of environmentallaw and their impact on the development of the national legislation of the Republic of Kazakhstan.These days Kazakhstan is directly involved in the process of international legal cooperation in thefield of environmental protection and rational use of natural resources. In this regard, the issues of recognitionand adoption at the domestic level of the norms and principles of international environmental andlegal cooperation, as well as determining their place in the system of sources of national environmentallaw, are of particular importance. In the current interconnected and interdependent world, the specialrole of inter-state regulation of the most pressing problems of mankind is becoming increasingly clear;among these problems directly and indisputably are, first of all, the problems of environmental protectionand its preservation for the benefit of present and future generations. The rules developed in theprocess of such interaction of states, united in an international agreement, cannot act in isolation withoutinteracting with the rules of domestic law. Moreover, such interaction is demonstrated in the allocationof a special category of sources (normative legal acts) of an international character in the general systemof sources of domestic law; and the constitutional and legal perception of international agreement normscan be characterized by the recognition of a separate, special preferential position of such norms overthe norms of national laws. In conclusion, the author presents theoretical statements, as well as practicalrecommendations on improving the existing environmental legislation of the Republic of Kazakhstan.Key words: environmental legislation, sources of law, implementation, norms of international law,national legislation.